Case report: Psychotherapy for enhancing psychological adjustment to dysphoric milk ejection reflex - Deif, Reem (Frontiers in Psychiatry, 2024)
Given its endless benefits, breastfeeding is widely acknowledged as the optimal choice for both maternal and infant health. Nevertheless, breastfeeding mothers often encounter various challenges that may hinder their ability to fully embrace this experience. This report delves into a compelling case of Dysphoric Milk Ejection Reflex (D-MER), a largely underexamined mental health issue among lactating mothers. D-MER is characterized by intense aversion right before milk let down, which can significantly impede a mother's willingness to breastfeed. The primary aim of this case report is to provide a comprehensive psychological understanding of D-MER, emphasizing aspects of attachment, the transition into motherhood, and the sociocultural sexualization of the female body. We also offer an overview of the psychotherapeutic journey, highlighting key insights and progress achieved over a span of six months. Therapy adopted an integrative approach combining narrative techniques and skills training such as mindfulness to facilitate a comprehensive therapeutic experience. This case underscores the psychological dimensions of the breastfeeding experience, complementing the well-established biochemical and physiological aspects of D-MER. It also emphasizes the need for further research into the psychological facets of both successful and less successful breastfeeding experiences.